Tindak Ekspresif Siswa Dalam Mengungkapkan Kesan Dan Pesan terhadap Aktivitas Mahasiswa Program Pengalaman Lapangan Di Sma Muhammadiyah 2 Surakarta - Andiani, Mei, Prof. Dr. Harun Joko Prayitno, M.Hum (2016)
This study has two objectives. (1) To describe the form of the expressive act of the students in revealing impressions and messages to the student activities program field experience at SMA Muhammadiyah 2 Surakarta. (2) To identify strategies follow-expressive students in revealing impressions and messages to the student activities program field experience at SMA Muhammadiyah 2 Surakarta. This study uses a qualitative method. The research was conducted on August 12 until October 19, 2015. The location of the research is SMA Muhammadiyah 2 Surakarta is located at Jl. Yosodipuro No. 95 Surakarta. To obtain the data carried by the listening process, with techniques refer to have the basic techniques such as tapping techniques and advanced engineering techniques in the form of notes. Analysis of the data in this study using a unified method. The results showed that: First, follow-expressive form students in revealing impressions and messages found 6 expression expressive form. (1) Being expressive form A sympathetic mode consists of gratitude. (2) Being expressive of excitement in the form of pride consists mode of expression survived. (3) Being expressive of hatred in the form of highly dislike mode consists of hate speech. (4) Being expressive pleasure in the form of convenient mode consists of a proud expression. (5) Being expressive of misery in the form of difficulty modes consist of the expression of criticism. (6) Being expressive difficulty in the form of distress mode consists of a disappointed expression. Second, the strategy acts expressive students in revealing impressions and messages found 3 action strategy said. (1) Strategy literal speech acts directly articulated speech mode and the same meaning with the intent pengutaraannya. (2) Strategy indirect speech acts literal phrased sentence mode that does not comply with the intent pengutaraannya, but the meanings of words are arranged according to what the speaker meant. (3) The strategy is not literal speech acts directly phrased sentences mode consistent with the intent of speech, but the words of which it is composed do not have the same meaning for the purpose statement.